PEMBELAJARAN GARIS LURUS DENGAN MODEL ELICITING ACTIVITIES DAN TEAM ASSISTED INDIVIDUALIZATION DITINJAU DARI GAYA KOGNITIF - Ari Suningsih, author (JURNAL E-DUMATH, 2015)
The aims of the research were to determine to the effect of learning models on mathematics achievement viewed from students cognitive style. The learning model compared were model elicting activities, team assisted Individualition, and direct instruction. The kind of research was a quasi experimental research with 3 x 2 factorial design. The population was the students of Junior high school in SMP N Pringsewu. The size of the sample was 208 students. The instruments used were mathematics achievement test and questionnaire. Hypothesis analysis test used two ways analysis of variance with unbalanced cells. The conclusions were as follow. model elicting activities gave better mathematics learning achievement than the students who used Cooperative Learning TAI type and Direct Instruction Assisted Powerpoint, and the students who used Cooperative Learning TAI type gave better mathematics learning achievement than the students who used Direct Instruction Assisted Powerpoint; For all types of students cognitive style give the different effect for mathematics learning achievement of students, In each model of learning, students with cognitive style types field independent gave better mathematics learning achievement than field dependent.Keywords: Kooperatif; MEas; TAI; Gaya Kognitif